The mechanism of training cadets in belt wrestling - Mirzayev Abdulxamit Marifovich (Periodica Journal, 2025)
The relevance of the analysis of traditional belt wrestling is largely due to the recently increased interest of the population in the national culture, a peculiar desire to avoid industrial monotony in the everyday life. In this regard, scientific development of the topic can contribute to the preservation and revival of the cultural and national heritage, solving cultural-restorative and educational problems. Materials. The significance of the study is also caused by the cognitive and practical interest in ethnographic and historical models of strengthening and preserving ethnicity. The methodological basis of the work is an integrated approach. It consists in using the cognitive capabilities of various sources that describe belt wrestling, as well as in its comprehensive study. Research methods: analysis of scientific and methodological literature, comparison, juxtaposition, historical analogy method. The modern system of understanding belt wrestling emphasizes its growing and multifaceted role in society. Belt wrestling performs a number of socially defined functions, and, first of all, the function of interethnic unity of peoples with different cultures, customs, etc. Belt wrestling is one of the most ancient sports. Ancient manuscripts, documents and various historical monuments of art tell us about it.
Keywords: Match; opponent; intensity; skill